Do central bank reforms lead to more monetary discipline? - Alexander Jung; Davide Romelli; Étienne Farvaque (European Central Bank (ECB), 2025)
This paper investigates the impact of reforms altering legal central bank independence (CBI) on monetary policy discipline and credibility, two key mechanisms shaping price stability. Using a sample of 155 countries over more than 50 years (1972-2023), we show that reforms improving CBI strengthen monetary discipline and the credibility of central banks. Larger reforms enhance monetary discipline with a lag, achieving their full effect after ten years. Central bank reforms have a greater impact on monetary discipline in countries that have not reversed earlier reforms. CBI reforms have the strongest impact in democratic countries, countries with flexible exchange rates, and those without a monetary policy strategy. The effects of CBI on monetary discipline and credibility are amplified when public debt-to-GDP ratios are high. These findings underscore the crucial role of CBI as a key factor influencing price stability and highlight the risks associated with weakening institutional autonomy.
Keywords: C21; C23; E42; E52; E58; 330; Independence; Money growth; Monetary policy; Institutional reforms; Local projections